Dual-Band 2 × 2 MIMO Antenna with Compact Size and High Isolation Based on Half-Mode SIW - Abubaker Ahmed Elobied; Xue-Xia Yang; Ningjie Xie; Steven Gao (International Journal of Antennas and Propagation)
This paper presents a close-spaced dual-band 2 × 2 multiple-input multiple-output (MIMO) antenna with high isolation based on half-mode substrate integrated waveguide (HMSIW). The dual-band operation of the antenna element is achieved by loading a rectangular patch outside the radiating aperture of an HMSIW cavity. The HMSIW cavity is excited by a coaxial probe, whereas the rectangular patch is energized through proximity coupling by the radiating aperture of HMSIW. The antenna elements can be closely placed using the rotation and orthogonal arrangement for a 2 × 2 array. Small neutralization lines at the center of the MIMO antenna can increase the isolation among its elements by around 10 dB in the lower band and 5 dB in the higher band. A prototype of the MIMO antenna is fabricated and its performance is measured. The measured results show that the resonant frequencies are centered at 4.43 and 5.39 GHz with bandwidths of 110 and 80 MHz and peak gains of 6 and 6.4 dBi, respectively. The minimum isolation in both bands is greater than 35 dB. The envelope correlation coefficient is lower than 0.005 within two operating bands.